Key Factors Influencing Vietnam REDD+ Participation. (16th March 2023) - Le, Hai Dinh; Dang, Ha Thi Hai; Harrison, Steven
ABSTRACT: There is a wide range of potential factors directly and indirectly influencing the decision of households participating in Reducing emissions from deforestation and forest degradation (REDD + ) programs. These potential factors can be grouped into characteristics of household heads, household characteristics, awareness of households on REDD+ program, and REDD+ policies factors. In this study, a survey conducted of 250 households (including 125 households participating and 125 non-participants in REDD+ program) in Ban Cam commune, Bao Thang district, Lao Cai province (150 households); and in Muong Phang commune, Dien Bien district, Dien Bien province (100 households), Vietnam. Binary logistic regression was used to identify key factors that significantly affect the decisions of households participating in REDD + programs in the study area. Six key factors influencing household participation in REDD + programs in the study area were identified, namely ethnicity, forestland area, educational level of household head, concern about forest degradation, equal distribution of government payment, and understanding of benefit on REDD + . The findings of this research provide implications for solution development, with the aim being to encourage participation of local households in REDD + programs in the study area.